2013
DOI: 10.3390/biom3030369
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Amylose Supramolecules in Form of Inclusion Complexes by Phosphorylase-Catalyzed Enzymatic Polymerization

Abstract: This paper reviews the architecture of amylose supramolecules in form of inclusion complexes with synthetic polymers by phosphorylase-catalyzed enzymatic polymerization. Amylose is known to be synthesized by enzymatic polymerization using α-d-glucose 1-phosphate as a monomer, by phosphorylase catalysis. When the phosphorylase-catalyzed enzymatic polymerization was conducted in the presence of various hydrophobic polymers, such as polyethers, polyesters, poly(ester-ether), and polycarbonates as a guest polymer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…1 Phosphorylase-catalyzed enzymatic polymerization to produce amylose complexation of amylose with polymeric guest molecules (Kadokawa 2011(Kadokawa , 2012(Kadokawa , 2013(Kadokawa , 2014Kadokawa and Kobayashi 2010;Kaneko and Kadokawa 2005). 1 Phosphorylase-catalyzed enzymatic polymerization to produce amylose complexation of amylose with polymeric guest molecules (Kadokawa 2011(Kadokawa , 2012(Kadokawa , 2013(Kadokawa , 2014Kadokawa and Kobayashi 2010;Kaneko and Kadokawa 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1 Phosphorylase-catalyzed enzymatic polymerization to produce amylose complexation of amylose with polymeric guest molecules (Kadokawa 2011(Kadokawa , 2012(Kadokawa , 2013(Kadokawa , 2014Kadokawa and Kobayashi 2010;Kaneko and Kadokawa 2005). 1 Phosphorylase-catalyzed enzymatic polymerization to produce amylose complexation of amylose with polymeric guest molecules (Kadokawa 2011(Kadokawa , 2012(Kadokawa , 2013(Kadokawa , 2014Kadokawa and Kobayashi 2010;Kaneko and Kadokawa 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of binding directly toward polymeric guest molecules into the cavity has been found, because the driving force for complexation is implied by weak hydrophobic interaction [3,4,5,6,7,8,9,10,11,12]. We have developed an efficient method for the formation of inclusion complexes from amylose and polymeric guest molecules by means of enzymatic polymerization [13,14,15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylase-catalyzed enzymatic polymerization occurs by using α - d -glucose 1-phoshate (G-1-P) as a monomer and maltooligosaccharide as a primer according to the following reversible reaction: ( α (1→4)-G) n + G-1-P ⇄ ( α (1→4)-G) n+1 + P. In the reaction, a glucose (G) residue is transferred from G-1-P to the non-reducing 4-OH propagating terminus of a α (1→4)-glucan chain, liberating inorganic phosphate (P). We have found that inclusion complexes are gradually formed with the progress of propagation when the phosphorylase-catalyzed enzymatic polymerization was carried out in the presence of hydrophobic guest polymers dispersed in an aqueous buffer solvent (Figure 1a) [13,14,15,16,17,18,19,20]. The process of propagation from the shorter α (1→4)-glucan chain (maltooligosaccharide primer) to the longer α (1→4)-glucan chain (amylose) efficiently induces complexation with polymeric guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation proceeds through the following reversible reaction to produce amylose: [α-(1 → 4)-G] n + G-1-P ⇄ [α-(1 → 4)-G] n+1 + Pi. [30][31][32][33][34][35] Recently, by means of the vine-twining polymerization approach using designed polymeric guests, we have achieved the fabrication of supramolecular hydrogels through inclusion complexation by amylose. We have found that the propagation of the phosphorylase-catalyzed enzymatic polymerization proceeded with the formation of inclusion complexes when the polymerization was performed in a dispersion of appropriate hydrophobic polymers as guest compounds, such as the well-known biodegradable polyester, poly-(ε-caprolactone) (PCL), with an aqueous buffer solution as a polymerization solvent.…”
Section: Introductionmentioning
confidence: 99%